PENGARUH HARGA,KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDI LAYANAN INTERNET INDOSAT OOREDOO DI JAKARTA TIMUR) - Muhamad Iqbal, (2023)
This research was conducted to study and analyze the effect of price, product quality and promotion on purchasing decisions (Study of Indosat Ooredoo Internet Services in East Jakarta). This study was conducted with respondents using Indosat Ooredoo internet services in East Jakarta. Data collection uses gfrom and has collected 100 respondents. This research was conducted quantitatively and descriptively using SmartPLS and purposive sampling method. This study states that price has a positive and significant effect on purchasing decisions. Product quality has a positive and significant influence on purchasing decisions. Promotion on purchasing decisions, has a positive and significant influence.